Associations between instrumented mouthguard-measured head acceleration events and post-match biomarkers of astroglial and axonal injury in male amateur Australian football players - Evans, L. J.; O`Brien, W. T.; Spitz, G.; Mutimer, S.; Xie, B.; Giesler, L. P.; Major, B. P.; Hickey, J. W.; Roberts, S. S. H.; Mitra, B.; O`Brien, T. J.; Shultz, S. R.; et al. (Sports Medicine, 2025)
Background: Advances in instrumented mouthguards (iMGs) allow for accurate quantification of single high-acceleration head impacts and cumulative head acceleration exposure in collision sports. However, relationships between these measures and risk of brain cell injury remain unclear. Aim: The purpose of this study was to quantify measures of non-concussive head impact exposure and assess their association with blood glial fibrillary acidic protein (GFAP), neurofilament light (NfL) and phosphorylated-tau-181 (p-tau-181) levels in male Australian football players. Methods: A total of 31 athletes underwent in-season (24 h post-match) and post-season (> 5 weeks) blood collections and/or wore HITIQ Nexus A9 iMGs measuring peak linear (PLA) and rotational (PRA) acceleration. Match footage was used to verify and code impacts. Blood GFAP, NfL, and p-tau-181 were quantified using Simoa and natural log transformed for analysis. Associations between post-match biomarkers and within match maximum single impact and cumulative PLA/PRA were assessed with linear mixed models. Results: In-season versus post-season elevations were found for GFAP (mean difference 0.14, 95% CI 0.01-0.26, p = 0.033), NfL (mean difference = 0.21, 95% CI 0.09-0.32, p = 0.001) and p-tau-181 (mean difference = 0.49, 95% CI 0.33-0.65, p < 0.001). Post-match GFAP was associated with maximum single impact PLA (B = 0.003, 95% CI 0.0002-0.005, p = 0.036), cumulative PLA (B = 0.001, 95% CI 0.0002-0.002, p = 0.017), cumulative PRA (B = 0.01, 95% CI 0.002-0.02, p = 0.014), and impact number (B = 0.03, 95% CI 0.003-0.05, p = 0.029) within a single match. Change in NfL levels between two-matches correlated with cumulative PLA (r = 0.80, 95% CI 0.38-0.95, p = 0.005), PRA (r = 0.71, 95% CI 0.19-0.92, p = 0.019) and impact number (r = 0.63, 95% CI 0.05-0.89, p = 0.038). Conclusion: Maximum and cumulative head accelerations in Australian football, measured by iMGs, were associated with elevated blood biomarkers of brain injury, highlighting the potential of both technologies for head impact management in collision sports.